2020
DOI: 10.1016/j.amjmed.2020.03.026
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Presentation of Novel Coronavirus Disease 2019 (COVID-19)

Abstract: Figure legendFigure 1 A, B, Computed tomography of chest showing groundglass densities present bilaterally, extending from the hilum, more prominent toward the periphery in the left upper lobe and middle lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 1 publication
3
69
0
Order By: Relevance
“…Atypical presentations of other infectious diseases, such as delirium with urinary tract infections, have been well described in frail, older adults and long-term care residents. Case reports of atypical presentations of COVID-19 include delirium as a presenting symptom, 16 , 17 , 18 and a high prevalence of delirium has been reported among patients with COVID-19 in intensive care units. 19 A case-series of hospitalized patients from Wuhan, China with COVID-19 infection reported 7.5% experienced impaired consciousness or delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical presentations of other infectious diseases, such as delirium with urinary tract infections, have been well described in frail, older adults and long-term care residents. Case reports of atypical presentations of COVID-19 include delirium as a presenting symptom, 16 , 17 , 18 and a high prevalence of delirium has been reported among patients with COVID-19 in intensive care units. 19 A case-series of hospitalized patients from Wuhan, China with COVID-19 infection reported 7.5% experienced impaired consciousness or delirium.…”
Section: Discussionmentioning
confidence: 99%
“…The virus was identified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the World Health Organization designated the disease as coronavirus disease 2019 (COVID- 19). The most common symptoms are respiratory, but gastrointestinal, neurological, and other atypical symptoms can also be seen, although these symptoms are rare [2]. Recent studies showed several coagulation abnormalities in patients with COVID-19, raising questions about appropriate management to prevent or treat thrombosis; this state has been termed COVID-19-associated coagulopathy (CAC) [3].…”
Section: Introductionmentioning
confidence: 99%
“…While these issues are obviously important, our report is restricted to patients presenting with syncope and presyncope. Thus far, syncope has only been reported in the COVID‐19 literature as two isolated case reports and a case series of five patients 12,15,16 . The case reports describe two elderly patients; one presenting with syncope followed by altered mental status and the other with antecedent influenza like symptoms and syncope after a bowel movement.…”
Section: Discussionmentioning
confidence: 99%